The potential role of echocardiographic strain imaging for evaluating cardiotoxicity due to cancer therapy - Stoodley, Paul W.; Richards, David A.B.; Meikle, Steve R.; Clarke, Jillian; Hui, Rina; Thomas, Liza (Heart, lung & circulation, 2011)
Refinements to conventional treatment and the development of new therapies have led to significant improvements in cancer survival. Yet, many frontline cancer treatments continue to be hindered by their significant side effects, amongst which cardiotoxicity is particularly important. Therefore, the focus of cancer management has changed; treatment is no longer aimed solely at overcoming malignancy, but emphasises early identification and treatment of potential side effects. In this regard, the cardiotoxic potential of certain anticancer agents mandate close monitoring of cardiac function, and the method of choice for monitoring is transthoracic echocardiography. Whilst this method has its limitations, a newer echocardiographic technique called myocardial strain imaging has the potential to detect early sub-clinical changes in cardiac function due to cardiotoxicity. Strain analysis has been the subject of several recent studies to evaluate its potential in monitoring cardiotoxicity, and this article reviews the recent literature and explores the potential role of myocardial strain imaging in cancer management and avenues for future research.